Infarcted Myocardium-Primed Dendritic Cells Improve Remodeling and Cardiac Function After Myocardial Infarction by Modulating the Regulatory T Cell and Macrophage Polarization. Issue 15 (11th April 2017) - Choo, Eun Ho; Lee, Jun-Ho; Park, Eun-Hye; Park, Hyo Eun; Jung, Nam-Chul; Kim, Tae-Hoon; Koh, Yoon-Seok; Kim, Eunmin; Seung, Ki-Bae; Park, Cheongsoo; Hong, Kwan-Soo; Kang, Kwonyoon; et al.
Abstract : Background: Inflammatory responses play a critical role in left ventricular remodeling after myocardial infarction (MI). Tolerogenic dendritic cells (tDCs) can modulate immune responses, inducing regulatory T cells in a number of inflammatory diseases. Methods: We generated tDCs by treating bone marrow–derived dendritic cells with tumor necrosis factor-α and cardiac lysate from MI mice. We injected MI mice, induced by a ligation of the left anterior descending coronary artery in C57BL/6 mice, twice with tDCs within 24 hours and at 7 days after the ligation. Results: In vivo cardiac magnetic resonance imaging and ex vivo histology confirmed the beneficial effect on postinfarct left ventricular remodeling in MI mice treated with tDCs. Subcutaneously administered infarct lysate–primed tDCs near the inguinal lymph node migrated to the regional lymph node and induced infarct tissue–specific regulatory T-cell populations in the inguinal and mediastinal lymph nodes, spleen, and infarcted myocardium, indicating that a local injection of tDCs induces a systemic activation of MI-specific regulatory T cells. These events elicited an inflammatory-to-reparative macrophage shift. The altered immune environment in the infarcted heart resulted in a better wound remodeling, preserved left ventricular systolic function after myocardial tissue damage, and improved survival. Conclusions: This study showed that tDC therapy in a preclinical model of MI was potentially translatable into an antiremodeling therapy for ischemic tissue repair. Abstract : Supplemental Digital Content is available in the text.